FUNCTIONAL ACTIVITY OF PLATELETS FOR THE PATIENTS WITH CHRONICAL GENERELIZED PERIODONTITIS AND CORRECTION OF THE HYPERAGREGATIONAL CHANGES IN THE COMPLEX TREATMENT BY THE GINKGO BILOBA EXTRACT - N.M. Pavelko; L.V. Tarnavska; H.B. Kimak; V.S. Dombrovych (Український стоматологічний альманах)
The presented results determine the functional activity of platelets in 35 patients diagnosed with chronic generalized periodontitis (CGP). Dystrophic changes in the periodontium were assessed by measuring pathological periodontal pockets and the Ramfjord index. The level of inflammation in periodontal tissues was determined by PMA and PBI indices.